Polarization switching characteristics of 0.5BaTi(0.8)Zr(0.2)O(3)-0.5Ba(0.7)Ca(0.3)TiO(3) lead free ferroelectric thin films by pulsed laser deposition - Kolekar, Y. D.; Bhaumik, A.; Shaikh, P. A.; Ramana, C. V.; Ghosh, K. (JOURNAL OF APPLIED PHYSICS, 2014)
We report on the ferroelectricity for morphotropic-phase-boundary lead (Pb) free 0.5BaTi(0.8)Zr(0.2)O(3)-0.5Ba(0.7)Ca(0.3)TiO(3) (0.5BZT-0.5BCT) thin films. Thin films were grown on Pt/Ti/SiO2/Si substrate using pulsed laser deposition. Raman spectroscopic data combined with the X-ray diffraction analyses confirm body centered tetragonal crystallographic structure 0.5BZT-0.5 BCT thin films on Pt/Ti/SiO2/Si. Polarization studies demonstrate that these 0.5BZT-0.5BCT films exhibit a large remnant and saturation polarization of 37 mu C/cm(2) and 40 mu C/cm(2), respectively, with a coercive field of 140 kV/cm. A correlation between polarization dynamics, structural distortion, and phonon vibration is established. The splitting of X-ray diffraction peak of the thin film in the 2 theta range of 44.5 degrees to 46.5 degrees represents high degree of tetragonality. The tetragonality factor calculated by Rietveld analysis was found to be 0.006 and can be a major cause for the increased remnant polarization value. It is established from Raman spectra that the non-centrosymmetricity due to the displacement of Ti/Zr ions from its octahedral position is related to the peak position as well as the broadening of the A(1) (LO) optical phonon mode. This increase of broadness in the thin film causes an increase in the dipole moment of the unit cell and, hence, the net increase in polarization values. (C) 2014 AIP Publishing LLC.